FeCl3-Promoted Facile Synthesis of Multiply Arylated Nicotinonitriles - Iwai, Kento; Yamauchi, Haruka; Yokoyama, Soichi; Nishiwaki, Nagatoshi (Synthesis, 2022)
Many biologically active nicotinonitriles have been reported to date. Consequently, the development of synthetic methods for multiply arylated/alkylated nicotinonitriles remains a sought-after field of research. In the present work, a new synthetic strategy for multi-substituted nicotinonitriles is described. A FeCl3-promoted condensation–cyclization reaction of an enamino nitrile and α,β-unsaturated ketones proceeded efficiently with a wide range of substrates. It is noteworthy that this method facilitates access to fully and differently substituted nicotinonitriles, including tetra-arylated nicotinonitriles, in only three steps. Using the functionality of the cyano group, the copper-catalyzed annulation reaction of the nicotinonitrile was achieved to yield benzo[c][2,7]naphthyridin-5(6H)-one.
Keywords: polysubstituted nicotinonitrile; iron(III) chloride; enamino nitrile; α,β-unsaturated ketone